OUTSOURCING AND WORKFORCE MANAGEMENT AT PT INDOFARM SUKSES MAKMUR ACCORDING TO LAW NO. 13 OF 2003 ABOUT EMPLOYMENT - Dody Partogi Nadeak; Anissa Zahra; Luhut Leonard (NOMOI Law Review, 2021)
Protection Rules that apply to workers As the fulfillment of inherent core rights / there is stipulated in the constitution contained in one of the articles in the 1945 Constitution,due to the enactment ofemployers as if accepting the legalization of enforcing pre-employment outsourcing regardless of the things that are stopped by the Law. The primary reason for outsourcing for the company is to increase the concentration of business because operational activities have been bestowed on other parties. This study will analyze the main conflicts that are in sync with the title using the scope of the problem that is going on, as already stated above using a normative juridical approach. Where this normative juridical approach is an approach that is done in accordance with the material of the primary rules by using basic principles and rules regulated through the laws and regulations in this study. The data is obtained, listed in the form of a concept model that will be the primary base in analyzing. As for thewritingof this scientific work the way used to analyze data has been taken using descriptive methods (non statistics). Legislation containing the content of employment as the basis in the step of setting the lower limit of workers' salaries to create and for the welfare of workers in north Sumatra province. The role of laws and rules on how to set the lower limit wages cannot help workers to achieve the adequacy of workers.